2020
DOI: 10.3389/fchem.2020.00073
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Limonoids From Cortex Dictamni

Abstract: The root barks of perennial herb Dictamnus dasycarpus (Cortex Dictamni) were reported to be rich in anti-inflammation activity constituents, limonoids. Then, the investigation of anti-inflammation therapeutic limonoids from this plant was developed in the present study. Through the combination of various chromatographies isolation, six new limonoids, named dictamlimonol A (1), dictamlimonoside B (2), and dictamlimonols C-F (3-6), along with seven known ones (7-13), were obtained. Their structures were ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Cortex dictamni is a traditional Chinese medicine used to treat diseases such as skin inflammation, rubella, eczema, rheumatism, and gynecologic inflammations (Chen et al, 2020). Previous phytochemical studies have revealed that limonoids and quinoline alkaloids are the main characteristic constituents of C. dictamni (Gao et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Cortex dictamni is a traditional Chinese medicine used to treat diseases such as skin inflammation, rubella, eczema, rheumatism, and gynecologic inflammations (Chen et al, 2020). Previous phytochemical studies have revealed that limonoids and quinoline alkaloids are the main characteristic constituents of C. dictamni (Gao et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Its molecular formula, C 47 H 78 O 17 ( m / z 913.51648 [M − H] − ; calcd. for C 47 H 77 O 17 , 913.51553) was measured on the negative-ion ESI-Q-Orbitrap MS. d -glucose and d -xylose were detected in its acid hydrolysis product by HPLC analysis [ 9 ]. The 1 H and 13 C NMR ( Table 1 ) spectra showed signals for eight methyl groups at δ 0.82, 0.94, 1.01, 1.11, 1.31, 1.51, 1.68, and 1.83 (3H each, all s, H 3 -19, 18, 29, 30, 28, 21, 26, and 27), three oxygenated methines at δ 3.37 (1H, dd, J = 4.5, 11.5 Hz, H-3), 3.67 (1H, m, H-12), and 4.86 (1H, dd, J = 8.0, 10.0 Hz, H-23), one tri-substituted olefin group at δ 5.55 (1H, d, J = 8.0 Hz, H-24), two β- d -glucopyranosyl moieties at δ 4.97 (1H, d, J = 8.0 Hz, H-1′) and 5.12 (1H, d, J = 8.0 Hz, H-1″), and one β- d -xylopyranosyl group at δ 4.99 (1H, d, J = 7.5 Hz, H-1‴), which suggested that notoginsenoside NL-I ( 1 ) was a dammarane-type triterpene saponin.…”
Section: Resultsmentioning
confidence: 99%
“…Acid Hydrolysis of 1 and 2 : Compounds 1 and 2 were hydrolyzed by 1M HCl and aqueous layers were obtained by using the reported method [ 9 ]. As the results shown, d -glucose and d -xylose were detected in their acid hydrolysate.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported the chemical properties and pharmacological activities of limonoids, including their structure–activity relationship [ 27 ]. Recently, the anti-inflammatory activities of limonoids and limonoid glucosides were reported [ 28 ]. Therefore, we sought to determine the effects of the limonoids isolated from C. junos seeds on inflammatory responses using two in vitro models, RAW 264.7 mouse macrophage cells and HT-29 colon epithelial cells, which can simulate the characteristics of intestinal epithelial cells in IBD.…”
Section: Discussionmentioning
confidence: 99%